Pengaruh Current Ratio (CR), Net Profit Margin (NPM) Dan Earning Per Share (EPS) Terhadap Price To Book Value (PBV) Pada PT. Gudang Garam Tbk, Periode 2015-2024 - Hikmatul Baidoh; Fakung Rahman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Current Ratio (CR), Net Profit Margin (NPM), and Earning Per Share (EPS) on Price to Book Value (PBV) at PT Gudang Garam Tbk for the period 2015–2024. This study uses secondary data with quantitative descriptive methods and an associative approach. The research population consists of PT Gudang Garam Tbk's annual financial reports during the research period. Data analysis includes descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing using t-tests, F-tests, correlation coefficients, and determination coefficients with the help of SPSS Version 26 software. The results show that, partially, the Net Profit Margin (NPM) variable has a significant effect on Price to Book Value (PBV), while Current Ratio (CR) and Earning Per Share (EPS) do not have a significant effect on PBV. However, based on the simultaneous test results, CR, NPM, and EPS together have a significant effect on PBV. The correlation coefficient test results show an R value of 0.909, which means there is a very strong relationship between the independent variables and the dependent variable. Meanwhile, the results of the coefficient of determination test show an Adjusted R Square value of 0.739, indicating that CR, NPM, and EPS are able to explain 73.9% of the variation in PBV, while the rest is influenced by other variables outside the research model. Thus, it can be concluded that Net Profit Margin (NPM) is the most dominant variable influencing Price to Book Value (PBV) at PT Gudang Garam Tbk during the research period.